Negative pressure wound therapy for the treatment of sternal wound infections after cardiac surgery. Issue 3 (3rd September 2012) - Fleck, Tatjana; Fleck, Michael
<x xml:space="preserve">Abstract</x> We retrospectively collected and analysed data from patients with sternal wound infections between 1995 and 2001, which were treated with different wound management strategies, and compared them with our patients from 2002 to 2011, who were treated with the sternal negative pressure wound therapy (NPWT). From 1995 to 2001, a total of 198 patients (group A) with a mean age of 65 ± 10 years developed sternal wound infection (67% deep) after cardiac surgery. Wound management consisted of surgical debridement and immediate sternal closure or open packing. From 2002 to 2011, a total of 326 patients (group B) (71% deep) were managed with NPWT at the time of surgical debridement. Total mortality was 10% in group A and 3·6% in group B. Recurrence rates were 34 and 8·5%, respectively, for the groups A and B. The meantime of NPWT was 11 days. In group B patients, 75% proceeded to sternal closure. With the introduction of NPWT, the treatment of sternal wound infections could be substantially improved. Particularly, the high recurrence rates could be minimised; furthermore, the goal to salvage the sternal bone is facilitated.